Heidegger, a técnica e a educação - Rodrigues, Raísla Girardi (2017)
This work aims to approach the German philosopher Martin Heidegger’s thinking with the theme of education. Heidegger thought in the 20th century about the question of the sense of being and the distinction between Dasein and other entities. He questioned how a human being perceives himself, gets involved, builds a world of meaning, uses the tools that are at his disposal, relates to other Dasein, with nature and with the world itself. Although not intentionally, such questions surround the educational field, when education is directed toward the formation of Dasein as a whole. The research adopted a hermeneutic perspective, trying to interpret Heidegger’s works and a set of texts of his most highly regarded commentators, seeking to unit such understandings to the analysis of education in today’s society, observing how it constitutes itself, for whom it is intended, what are its pros and cons when one thinks of formation that aims to go beyond the mere transmission of knowledge and development of practice as its guiding, not forgetting that it is essential to teach, but it is also fundamental to develop thinking, feelings and being in essence, human. Empathy, authenticity and care lose space in a pragmatic and technical worldview, which annihilates the more authentic possibilities of Dasein. To think about the implications of technology in today’s society is to understand that it becomes a framework in which reality and all that exists nevertheless fit into education. It is necessary to think of the ways, the dangers and the salvation that both technology and education can offer to the modern world. Education must be constantly under surveillance about how it presents itself to the Dasein, because in it rests the possibility of showing that the human being is unique, that the human being is not liable to manipulation and exploitation but rather to relations of care and of an authentic search of himself. Education opens space with philosophy to the question about the meaning of being, bringing up fundamental questions which seem to have been forgotten. It’s understood that both technology and education can have two biases, and the Dasein should choose between the imprisonment and the freedom they both offer.